An improved phenotyping method for evaluation of yam (Dioscorea spp.) resistance to nematodes belonging to the genera meloidogyne and scutellonema - Kolombia, Y.A.; Kumar, P.L.; Lopez-Montes, A.J.; Claudius-Cole, A.O.; Maroya, N.; Viaene, N.; Bert, W.; Coyne, D.L. (MDPI, 2024)
Phenotyping yam (Dioscorea spp.) germplasm for resistance to parasitic nematodes is hampered by the lack of an efficient screening method. In this study, we developed a new method using rooted yam vine cuttings and yam plantlets generated from semi-autotrophic hydroponics (SAHs) propagation for phenotyping yam genotypes for nematode resistance. The method was evaluated using 26 genotypes of D. rotundata for their reaction to Scutellonema bradys and four root-knot nematode species, Meloidogyne arenaria, M. enterolobii, M. incognita, and M. javanica. Yam plantlets established in nursery bags filled with steam-sterilized soil were used for screening against single nematode species. Plants were inoculated four weeks after planting and assessed for nematode damage eight weeks later. A severity rating scale was used to classify genotypes as resistant, tolerant, or susceptible determine based on the nematode feeding damage on tubers and the rate of nematode multiplication in the roots of inoculated plants. The results demonstrated putative resistance and tolerance against S. bradys in 58% of the genotypes and 88%, 65%, 65%, and 58% against M. arenaria, M. javanica, M. incognita, and M. enterolobii, respectively. The method is rapid, flexible, and seasonally independent, permitting year-round screening under controlled conditions. This method increases the throughput and speed of phenotyping and improves the selection process.